Anaesthesia for major spinal surgery. Issue 4 (April 2018) - Ho, Roger; Irwin, Michael G.
Abstract: Major spinal surgery is performed for a wide variety of conditions including degenerative diseases, scoliosis and autoimmune diseases. Anaesthesia often presents several challenges to the anaesthetist. Careful pre-anaesthetic assessment and planning is important as patients may have multiple comorbidities. Important perioperative issues to consider include aspects of airway management, neurophysiological monitoring, patient positioning, blood conservation strategies, pain management and specific complications such as perioperative visual loss.